2008
DOI: 10.1111/j.1475-3588.2007.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Untreated Psychosis, Referral Route, and Age of Onset in an Early Intervention in Psychosis Service and a Local CAMHS

Abstract: Background:  The aim of this study was to investigate associations between demographic and clinical variables and duration of untreated psychosis (DUP) in a sample of cases of psychosis across an adult early intervention in psychosis service and a child and adolescent community team. Method:  Cross‐sectional baseline data for cases of psychosis across the two teams on the caseload at a given time point were collected, including age of onset, gender, ethnicity, referral route, and DUP. Results:  The median DUP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Thus, early interventions to reduce DUP in this population must also focus on identifying and managing early psychosis in adolescents (Dominguez et al, 2013;Norman et al, 2004). However, another study found that younger age was associated with shorter DUP but proposed further investigations on this phenomenon (Kelso, Judith, Victoria, Mima, & Katherine, 2008 educated may lack understanding of the illness and may have ignorance toward the available service provisions (Basu, Subramaniam, Abdin, Poon, & Verma, 2015;Chee, Muhammad Dain, Abdul Aziz, & Abdullah, 2010;Lihong et al, 2012). This speculated difference in knowledge gap between the lower educated and the higher educated may implicitly emanate from the hypothesis that the higher educated could be well positioned than the lower educated in having access to information about the disease from various media sources (Tichenor, Donohue, & Olien, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, early interventions to reduce DUP in this population must also focus on identifying and managing early psychosis in adolescents (Dominguez et al, 2013;Norman et al, 2004). However, another study found that younger age was associated with shorter DUP but proposed further investigations on this phenomenon (Kelso, Judith, Victoria, Mima, & Katherine, 2008 educated may lack understanding of the illness and may have ignorance toward the available service provisions (Basu, Subramaniam, Abdin, Poon, & Verma, 2015;Chee, Muhammad Dain, Abdul Aziz, & Abdullah, 2010;Lihong et al, 2012). This speculated difference in knowledge gap between the lower educated and the higher educated may implicitly emanate from the hypothesis that the higher educated could be well positioned than the lower educated in having access to information about the disease from various media sources (Tichenor, Donohue, & Olien, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Nine of these studies had included at least 1 of the following terms in their title, abstract or introduction: "demographic, socioenvironmental (…) predictors" (Broussard et al, 2013), "social determinants" (Nishii et al, 2010) or even "African-American (…) patients" (Compton, Esterberg, Druss, Walker, & Kaslow, 2006;Compton, Goulding, Gordon, Weiss, & Kaslow, 2009), "demographic characteristics" (O'Donoghue et al, 2014),"ethnicity" (Clarke et al, 2007;Cratsley, Regan, McAllister, Simic, & Aitchison, 2008),"socio-demographic contributors" (Chon et al, 2015) or "demographic factors" (Al Fayez, Lappin, Murray, & Boydell, 2017). Nonetheless, they did not explore transcultural variables after the introduction and were therefore excluded.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that there is a need for early identification of psychosocial problems and the provision of services which do not necessarily require a medical diagnosis to access. Cratsley et al (2008) report that even for young people with psychosis referral times depend on whether presentation is to A&E or by a home referral team. These referral pathways result in quicker referral than through mainstream referral to Child and Adolescent Mental Health Services (CAMHS).…”
Section: Discussionmentioning
confidence: 99%